Exploring the motivations associated with the poaching and trafficking of Amur tigers in the Russian Far East - Skidmore, Allison (Deviant behavior, 2023)
Poaching for the illegal wildlife trade is the most direct threat to the persistence of Amur tigers. Despite the recognition that reducing poaching is necessary to prevent extinction, the motivations that drive this activity are not well understood. Understanding this behavior is the first critical step to implementing tangible policy solutions. This study utilizes ethnographic methods to gather empirical evidence about the motivations associated with the poaching and trafficking of Amur tigers in the Russian Far East. By conducting interviews with those directly involved in the illegal tiger trade, three main motivations are identified: status and impunity, poverty (both economic and cultural/traditional poverty), and human/tiger conflict. Economic factors, due to the value of tiger parts for traditional medicine in China, is by far the largest influence on poaching in Russia. It is facilitated and exacerbated by systemic structural inequalities between social classes, including unequal distribution of power and resources and embedded corruption.